Validación del método de Ensayo al Fuego para oro y plata de muestras minerales - Morales Arciniega, Santiago Daniel (2018)
Abstract:This work shows the results of the validation of the fire assay for gold and silver of mineral samples in which it shown by statistical calculations such as: linearity, limit of detection, limit of quantification, accuracy, precision and uncertainty, using certified reference substances to determine if the proposed method for the determination of these metals is adequate. The method proposed for the determination of these metals is based on the classic fire assay, so the analytical balance Ohaus is used for its final measurement which has a resolution of d=0.00001. The method for the determination of gold is suitable for its quantification, obtaining a veracity in which 80%<R<120%, coefficient of variation of repeatability and reproducibility of 5.97% and an expanded uncertainty of 12.49%. The method used in the laboratory is not suitable for the determination of silver since it does not comply with the statistical parameters, having a veracity in which the recovery is not within 80% and 120%, and a coefficient of variation of repeatability and reproducibility of 7.52% that is greater than the Horwitz variation coefficient.